2021
DOI: 10.3389/fvets.2021.694357
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Energy Level Impacts the Performance of Donkeys by Manipulating the Gut Microbiome and Metabolome

Abstract: Considerable evidence suggests that dietary energy levels and gut microbiota are pivotal for animal health and productivity. However, little information exists about the correlations among dietary energy level, performance, and the gut microbiota and metabolome of donkeys. The objective of this study was to investigate the mechanisms by which dietary energy content dictates the growth performance by modulating the intestinal microbiome and metabolome of donkeys. Thirty-six nine-month-old male Dezhou donkeys wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
2
3
1
Order By: Relevance
“…Additionally, an association was found between the structure of the rumen microbiota and metabolic profiles. These results were consistent with those in donkeys ( 64 ), yaks ( 65 ), Holstein heifers ( 18 ), mice ( 66 ) and humans ( 67 ), revealing a close relationship between microbiota, metabolites and organismal health. Our study also found significant positive correlations between the dominant bacterial groups and differential metabolites using Spearman correlation analysis.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, an association was found between the structure of the rumen microbiota and metabolic profiles. These results were consistent with those in donkeys ( 64 ), yaks ( 65 ), Holstein heifers ( 18 ), mice ( 66 ) and humans ( 67 ), revealing a close relationship between microbiota, metabolites and organismal health. Our study also found significant positive correlations between the dominant bacterial groups and differential metabolites using Spearman correlation analysis.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, an association was found between the structure of the rumen microbiota and metabolic profiles. These results were consistent with those in donkeys (64), yaks (65), Holstein heifers (18), mice (66) and humans (67), revealing a close relationship between microbiota, metabolites and organismal health. Our study also found significant positive correlations between the dominant bacterial groups and differential metabolites using Spearman correlation analysis.…”
Section: Discussionsupporting
confidence: 89%
“…The cecal metabolome was quantitatively measured following the procedure described in our previous paper using liquid chromatography-tandem mass spectrometry (LC-MS/MS) (Novogene Co., Ltd., Beijing, China). In brief, the measurement process contained three main steps: (1) metabolite extraction, (2) metabolites in the chyme were quantified by ultrahigh-performance liquid chromatography-tandem mass spectrometry (UHPLC–MS/MS) analysis, and (3) data processing and metabolite identification. , …”
Section: Methodsmentioning
confidence: 99%
“…In brief, the measurement process contained three main steps: (1) metabolite extraction, (2) metabolites in the chyme were quantified by ultrahigh-performance liquid chromatographytandem mass spectrometry (UHPLC−MS/MS) analysis, and (3) data processing and metabolite identification. 13,23 Calculations and Statistical Analysis. Data for growth performance including the BW, ADFI, ADG, and G:F were analyzed by one-way ANOVA according to Dunn's multiple comparisons using the IBM SPSS Statistics 23.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%